Cognitive Biases on Investment Decisions in the Nepalese Stock Market - Thapa, Bhim Kumar (Journal of Nepalese Business Studies, 2024)
This paper analyzes how behavioral biases impact investor decision-making regarding investment opportunities in Nepal. Purposive sampling was adopted, with participants comprising investors in the Nepalese stock market. An explanatory research design was used, employing a quantitative data collection method. The analysis was conducted using the structural equation modeling approach with the SPSS Amos program. The results demonstrated high reliability, discriminant validity, and convergent validity of the developed scale. Behavioral biases such as herding behavior, overconfidence, anchoring, and the disposition effect were found to have positive influences on investment decisions. These findings highlight the need to reduce biases in investment strategies to enhance the quality of decision-making. By incorporating Nepalese market data, this study addresses a significant gap in the literature on behavioral finance. It also provides valuable insights for investors, improving their perceptions and decision-making processes.